التناص في شعر خالد سعود الزيد - نعناع، محمد فؤاد (جامعة الكويت - مجلس النشر العلمي, 2010)
تهدف الدراسة إلى جلاء صورة التناص في شعر خالد سعود الزيد( )، وكان لابد من تمهيد أوجز فيه مفهوم التناص وتسمياته ومصادره وطرائقه وعلاقته بألوان بديعية وقضايا نقدية في تراثنا العربي البلاغي والنقدي. ثم حاولت بيان التناص في شعر الزيد، ووزعته على ثلاث دوائر، هي: التناص الديني، والتناص الصوفي، والتناص الأدبي والتاريخي والشعبي. This study aims to examine the phenomenon of intertextuality in Khaled Saoud. Al-Zayed’s verse. It starts with introducing the concept of intertextuality by addressing its definitions, resources and meth¬ods. After that, the study relates intertextuality to other figures of speech and relevant rhetorical issues in our medieval Arab heritage. This case study divides intertextuality in Al-zayed’s poetry into three categories: religious, literary, and historical/popular intertextuality.
Keywords: الزيد ، خالد سعود -- التناص -- الشعر العربي -- العصر الحديث -- نقد الشعر -- الكويت -- البلاغة العربية -- الشعر الاسلامي -- القرآن الكريم -- الشعر الصوفي -- الالفاظ -- الحداثة -- الشعراء الكويتيون